Evaluation of the soundscapes through the cafe terraces before and after the COVID-19 lockdown in coastal cities in Algeria. (July 2022) - Berkouk, Djihed; Bouzir, Tallal Abdel Karim; Boucherit, Samiha; Khelil, Sara; Mahaya, Chafik; Matallah, Mohamed Elhadi
This paper aimed to examine the impact of the COVID-19 lockdown in Algeria on the soundscapes' components throughout the cafe terraces in coastal cities. The methodology is based on a laboratory qualitative approach established and divided into two stages. And the monitoring of sound recordings through twenty-one cafe terraces inside the coastal city of Azzaba in Algeria was conducted before and after the lockdown of whole the country due to the COVID-19 pandemic. Using the McNemar's test on the first stage, results suggest that the lockdown measures in Algeria affect the soundscape components of the cafe terraces, specifically the predominance of the anthrophonical sounds over the natural sound components. The predominance of traffic sounds on the soundscapes after the lockdown period does not reflect an increase in noise level, whereas the soundscapes through the cafe terraces during the two periods were similar, and showed as less noisy by the semantic difference analysis evaluation, of the second stage. The factors of the principal component analysis suggest that the soundscapes of the cafe terraces reflect the main patterns of the acoustics design in the public spaces, such as functions (relaxation and communication), space-time for the two factors of the soundscapes of the period before the lockdown, and by relaxation, space and time for the three factors of those of the period after lockdown. Otherwise, the Marginal Homogeneity Test shows that there are significant differences in the assessment of the soundscapes of the cafe terraces during the two periods, which were only associated to the functions. Findings suggest that additional long-term research is needed to preserve and improve the cultural soundscapes among the urban spaces to ensure the acoustic comfort of the occupants and preserve their health.